Product-Led Growth Accounting: Linking Feature Adoption to Revenue Recognition and CAC Payback Dynamics - Blessing Olajumoke Farounbi; Omoize Fatimetu Dako; Ogochukwu Prisca Onyelucheya; Akindamola Samuel Akinola (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This study investigates the relationship between product-led growth (PLG) initiatives and financial performance metrics in subscription-based software businesses. Focusing on feature adoption, revenue recognition, and customer acquisition cost (CAC) payback dynamics, the research develops a framework to link user engagement patterns with financial outcomes. Using a mixed-methods approach combining longitudinal user analytics, cohort-based revenue analysis, and regression modeling, the study quantifies the impact of specific product features on customer monetization and cost recovery timelines. Findings indicate that early adoption of high-value features accelerates revenue recognition, shortens CAC payback periods, and strengthens unit economics. The research contributes to both academic literature and practical finance and product management, providing actionable insights for SaaS companies aiming to optimize product-led monetization strategies.